ANALYSIS OF DATABASE MODELS FOR ADVANCED AUTOMATED COMMAND AND CONTROL SYSTEMS - Vitalii A. Savchenko; Volodymyr M. Cherneha (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
The analysis of existent models of databases is carried out, advantages and disadvantages of every model are identified. Direction of researches for forming of structure and parameters of database model for perspective automated control system of troops is defined.